Approximate Determination of the ground-state Schroedinger Eigenfunction by Means of the Hypervirial Theorems Technique - Grypeos, M. E.; Liolios, T. E. (HNPS Advances in Nuclear Physics, 2019)
The method of the Hypervirial Theorems is used to obtain analytically the ground-state· Schroedinger eigenfunction for a wide class of potentials in non-relativistic Quantum Mechanics.The whole scheme, despite its simplicity, yields in many cases a good approximation.